High-performance Ruddlesden–Popper two-dimensional perovskite solar cells via solution processed inorganic charge transport layers. Issue 26 (22nd June 2022) - Liu, Zhihai; Wang, Lei; Xie, Xiaoyin; Xu, Chongyang; Tang, Jianfeng; Li, Wei
Abstract : Long-term stability and suppressed power-conversion efficiency degradation achieved with inorganic charge transport layers. Abstract : Two-dimensional (2D) layered halide perovskites have been shown to enable improved long-term stability in comparison to the well-known three-dimensional hybrid organic–inorganic halide perovskites. The optoelectronic properties of the 2D perovskites are strongly influenced by the chemical nature of the charge transport layer. In this work, we fabricated Ruddlesden–Popper 2D perovskite solar cells (PSCs) using solution processed inorganic NiO x and a C60 : C70 (1 : 1) mixture as the hole and electron transport layers, which significantly improved the performance of the 2D PSCs. Time resolved photoluminescence measurements indicate the shortened lifetime of excitons, which demonstrates the excellent charge extraction properties. The PSCs based on these inorganic charge transport materials (CTMs) exhibit an average power conversion efficiency (PCE) of 14.1%, which is higher than that (12.3%) of PSCs using organic CTMs of poly(3, 4-ethylenedioxythiophene) : poly(styrenesulfonate) (PEDOT:PSS) and phenyl-C61-butyric acid methyl ester (PCBM). Compared with PEDOT:PSS and PCBM based cases, the PSCs using inorganic CTMs also show improved long-term stability, with the PCE degradation significantly suppressed from 20% to 12% after a measurement of 15 days. The best PSCs using NiO x and C60 : C70 show a high PCE of 14.4%, with a stable power output and negligible hysteresis.